Dingo movement depends on sex, social status and litter size - Brendan F. Alting; Benjamin J. Pitcher; Michelle Campbell-Ward; Neil R. Jordan (Royal Society Open Science, 2025)
Territoriality constrains animal movement as resident individuals or social groups defend areas from non-residents. Here, we evaluated space use by dingoes, a territorial and socially monogamous group-living apex predator in Australia. We used data from remote camera traps and hourly fixes from GPS collars on eight individuals in five packs to identify variations in dingo territoriality and movement leading up to and including their annual breeding season, particularly in relation to an individual’s known social status, sex and competition within their pack. Subdominant male detections increased outside their pack’s home range during the breeding season, while subdominant female detections were unchanged. Furthermore, dominants spent more time (a higher proportion of detections) inside their territory as the number of pups present in their pack from the previous year increased. In common with other carnivores, these results suggest that ranging patterns depend on the sex and breeding status of the individual and potentially on levels of competition. Subdominant males may be exploring breeding opportunities outside of their own range, while dominants may remain in their territory to defend space, resources and reproductive partners. Understanding individual movement within and beyond their home range, can help to guide management actions both spatially and temporally.